Variability and transient search in the SUDARE–VOICE field: a new method to extract the light curves. Issue 3 (27th February 2020) - Liu, Dezi; Deng, Wenqiang; Fan, Zuhui; Fu, Liping; Covone, Giovanni; Vaccari, Mattia; Radovich, Mario; Capaccioli, Massimo; De Cicco, Demetra; Grado, Aniello; Marchetti, Lucia; Napolitano, Nicola; et al.
ABSTRACT: The VLT Survey Telescope (VST) Optical Imaging of the CDFS and ES1 Fields Survey, in synergy with the SUDARE survey, is a deep optical ugri imaging of the CDFS and ES1 fields using the VST. The observations for the CDFS field comprise about 4.38 deg 2 down to r ∼ 26 mag. The total on-sky time spans over 4 yr in this field, distributed over four adjacent sub-fields. In this paper, we use the multiepoch r -band imaging data to measure the variability of the detected objects and search for transients. We perform careful astrometric and photometric calibrations and point spread function modelling. A new method, referring to as differential running-average photometry, is proposed to measure the light curves of the detected objects. With the method, the difference of PSFs between different epochs can be reduced, and the background fluctuations are also suppressed. Detailed uncertainty analysis and detrending corrections on the light curves are performed. We visually inspect the light curves to select variable objects, and present some objects with interesting light curves. Further investigation of these objects in combination with multiband data will be presented in our forthcoming paper.